Assessing students' use of LinkedIn in a business and professional communication course. Issue 4 (1st October 2016) - Slone, Amanda Ruth; Gaffney, Amy L. H.
ABSTRACT: This paper examined the practice of using LinkedIn as a tool for teaching students how to create a professional online presence. A descriptive analysis of student LinkedIn profiles revealed that students included some basic requirements, but many students still neglected to fully complete the profile, thereby leaving out some important information that would boost their credibility. Additional exploratory analyses were conducted. Results are discussed in relation to contemporary best practices for the platform. Suggestions for the improvement of the assignment given to students to teach professional online presence through LinkedIn are also given.